Prospects for the Development of the Oil and Gas Industry in the Regional and Global Economy - Morozov, Ivan V.; Potanina, Yuliya M.; Voronin, Sergey A.; Kuchkovskaya, Natalia V.; Siliush, Mapo Dare (International Journal of Energy Economics and Policy, 2018)
Problems of energy efficiency, along with increasing environmental safety of production and increasing social responsibility, are becoming a central object of research. Therefore, the main goal of the work is to analyze the prospects for the development of the oil and gas industry. It was established that innovative technologies play an important role in the development of energy. In the structure of public administration, the definition of the place in the close relationship with commodity-money relations, mediating its implementation. But refusal of oil resources will lead to negative consequences. It is established that the maximum production of conventional oil in the world in the amount of 4.5-4.8 billion tons per year will be achieved in 2020-2030. Major areas of conventional oil production in this period will be oil and gas basins of the Persian Gulf, Western and Eastern Siberia, the Caspian sea, the Atlantic shelves of Africa and South America. The achieved level of oil production can be maintained by large-scale involvement in the development of non-traditional sources (bitumen and shale oil). According to the raw material base, the leaders of unconventional oil production should be Venezuela, Canada, Russia and the United States. Keywords: environmental policy, oil production, forecast, coal-fired power plants, economic crisis. JEL Classifications: L100, Q400, Q430.